RANCANG BANGUN SISTEM INFORMASI PENGGAJIAN PADA KOPERASI PEGAWAI MARITIM (KOPEGMAR) SUNDA KELAPA - Indra Hiswara; Andy Dharmalau; Surahman Surahman (Institut Teknologi dan Bisnis (ITB) Swadharma, 2021)
The improving the performance and service quality of a company requires information technology, so that the company can use it to carry out their daily activities. Computerization is intended so that work that is routine and requires accuracy can be done effectively and efficiently. Activities in the Sunda Kelapa Jakarta Maritime Employee Cooperative (Kopegmar) have a problem. The data on temporary employees is incomplete. The process of making payslips still frequently makes recording errors. In calculating the payroll of permanent employees, there are still frequent errors and slow payroll reporting. Methods of data collection by observation and interviews directly on the object of research. The result of the analysis is the absence of an archiving application system in the company so that it does not run well, because it is needed an application with a database system is expected to solve the problem. A systematic and efficient computer-based payroll information system design that is made in accordance with the needs and is very useful for the Sunda Kelapa Jakarta Maritime Employee Cooperative (Kopegmar).